The use of filamentous hemagglutinin adhesin to detect immune responses to Campylobacter hepaticus infections in layer hens - Muralidharan, Chithralekha; Quinteros, José A.; Anwar, Arif; Wilson, Timothy B.; Scott, Peter C.; Moore, Robert J.; Van, Thi Thu Hao (Frontiers in Veterinary Science, 2022)
Campylobacter hepaticus is the aetiological agent of Spotty Liver Disease (SLD). SLD can cause significant production loss and mortalities among layer hens at and around peak of lay. We previously developed an enzyme linked immunosorbent assay (ELISA), SLD-ELISA1, to detect C. hepaticus specific antibodies from bird sera using C. hepaticus total proteins and sera pre-absorbed with Campylobacter jejuni proteins. The high specificity achieved with SLD-ELISA1 indicated the presence of C. hepaticus specific antibodies in sera of infected birds. However, some of the reagents used in SLD-ELISA1 are time consuming to prepare and difficult to quality control. This understanding led to the search for C. hepaticus specific immunogenic proteins that could be used in recombinant forms as antibody capture antigens in immunoassay design. In this study, an immunoproteomic approach that combined bioinformatics analysis, western blotting, and LC MS/MS protein profiling was used, and a fragment of filamentous hemagglutinin adhesin (FHA), FHA1628-1899 with C. hepaticus specific antigenicity was identified. Recombinant FHA1628-1899 was used as antigen coating on ELISA plates to capture FHA1628-1899 specific antibodies in sera of infected birds. SLD-ELISA2, based on the purified recombinant FHA fragment, is more user-friendly and standardizable than SLD-ELISA1 for screening antibody responses to C. hepaticus exposure in hens. This study is the first report of the use of FHA from a Campylobacter species in immunoassays, and it also opens future research directions to investigate the role of FHA in C. hepaticus pathogenesis and its effectiveness as a vaccine candidate.